2022
DOI: 10.21203/rs.3.rs-2246792/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The distribution of vertebrate roadkill varies by season, surrounding environment and animal class

Abstract: Due to rapid human expansion in the last century, wildlife roadkill is becoming a concerning threat to biodiversity and human safety. The frequency of roadkill events depends on factors related to specific traits of the road –fencing, tortuosity, or type of habitat, among others– and the animal ecology –such as activity patterns, reproductive season, thermoregulation– which, in turn, are related to environmental factors (with seasonal variations). Here we assessed roadkill mortality of terrestrial vertebrates … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Temperature may better explain mammalian activity, which diminishes towards the extremes [44,51]. Here, roadkill of endothermic vertebrates as well as reptiles was positively influenced by daily low temperature—a trend observed in these classes elsewhere [38,40,42,92]. Our post-sunset sampling times coincided with when many Sonoran Desert reptiles, especially snakes, increase activity owing to more tolerable temperatures [60,65,68] and nocturnal mammals begin their surface activities [44,94].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Temperature may better explain mammalian activity, which diminishes towards the extremes [44,51]. Here, roadkill of endothermic vertebrates as well as reptiles was positively influenced by daily low temperature—a trend observed in these classes elsewhere [38,40,42,92]. Our post-sunset sampling times coincided with when many Sonoran Desert reptiles, especially snakes, increase activity owing to more tolerable temperatures [60,65,68] and nocturnal mammals begin their surface activities [44,94].…”
Section: Discussionmentioning
confidence: 96%
“…Environmental factors, such as climate, development, traffic and luminosity, are associated with road mortality [3741]. Roadkill rates can also vary temporally by diel and seasonal activity periods [42,43]. Many herpetofauna and small mammals, for example, employ nocturnal activity strategies to evade the heat of the day in desert climates [38,44]; herpetofauna often use roads for thermoregulation after the sun sets [34,35,45].…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to fully understand the impact of season and other factors on roadkill in the Afromontane forest of southwest Ethiopia, long term research is needed to account for the variability. Moreover, some studies reported that there is a seasonal variation in the number of wildlife road kills [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%